Amyloid fibrils degradation: the pathway to recovery or aggravation of the disease? - Maksim I. Sulatsky; Olga V. Stepanenko; Olesya V. Stepanenko; Ekaterina V. Mikhailova; Irina M. Kuznetsova; Konstantin K. Turoverov; Anna I. Sulatskaya (Frontiers in Molecular Biosciences, 2023)
Background: The most obvious manifestation of amyloidoses is the accumulation of amyloid fibrils as plaques in tissues and organs, which always leads to a noticeable deterioration in the patients’ condition and is the main marker of the disease. For this reason, early diagnosis of amyloidosis is difficult, and inhibition of fibrillogenesis, when mature amyloids are already accumulated in large quantities, is ineffective. A new direction for amyloidosis treatment is the development of approaches aimed at the degradation of mature amyloid fibrils. In the present work, we investigated possible consequences of amyloid’s degradation.Methods: We analyzed the size and morphology of amyloid degradation products by transmission and confocal laser scanning microscopy, their secondary structure and spectral properties of aromatic amino acids, intrinsic chromophore sfGFP, and fibril-bound amyloid-specific probe thioflavin T (ThT) by the absorption, fluorescence and circular dichroism spectroscopy, as well as the cytotoxicity of the formed protein aggregates by MTT-test and their resistance to ionic detergents and boiling by SDS-PAGE.Results: On the example of sfGFP fibrils (model fibrils, structural rearrangements of which can be detected by a specific change in the spectral properties of their chromophore), and pathological Aβ-peptide (Aβ42) fibrils, leading to neuronal death in Alzheimer’s disease, the possible mechanisms of amyloids degradation after exposure to factors of different nature (proteins with chaperone and protease activity, denaturant, and ultrasound) was demonstrated. Our study shows that, regardless of the method of fibril degradation, the resulting species retain some amyloid’s properties, including cytotoxicity, which may even be higher than that of intact amyloids.Conclusion: The results of our work indicate that the degradation of amyloid fibrils in vivo should be treated with caution since such an approach can lead not to recovery, but to aggravation of the disease.